Parathormone as a Risk Factor for Cardiac Dysfunction in Individuals Undergoing Hemodialysis (The Insight, 2025)
Background: Elevated parathyroid hormone (iPTH) levels have been associated with adverse cardiovascular outcomes in hemodialysis patients. This study aims to explore the relationship between elevated iPTH levels and cardiac dysfunction, with a focus on left ventricular ejection fraction (LVEF), left ventricular hypertrophy (LVH), and other cardiovascular markers. Objectives: To explore the role of parathyroid hormone (PTH) as a potential risk factor for cardiac dysfunction in individuals undergoing hemodialysis. Methods & Material: A total of 215 hemodialysis patients were enrolled and categorized into elevated iPTH and normal iPTH groups. Demographic data, dialysis duration, biochemical markers, and cardiovascular parameters, including LVEF, LVH, B-type natriuretic peptide (BNP), and carotid intima-media thickness (CIMT), were assessed. Logistic regression and multivariate linear regression were used to evaluate the relationship between iPTH and cardiovascular outcomes. Result: The elevated iPTH group had significantly lower LVEF (50.1% vs. 56.4%, p
Keywords: Elevated parathyroid hormone; cardiovascular dysfunction; hemodialysis; left ventricular ejection fraction; left ventricular hypertrophy